Working on optical characterization setup (fun experience of working with lasers!) for cutting-edge silicon photonics technology : part 1 - Chen, Deng Zhou (2019)
Photonic-integrated circuits (PICs) are the main catalyst for the ultimate miniaturization of various disruptive technologies such as Light Detection and Ranging (LiDAR) for autonomous vehicles, bio-chemical sensors and chip-level optical communication. Despite all these uses, the realization of fully functional PICs is limited by the absence of an efficient laser source on silicon, therefore making a practical silicon-compatible laser the Holy Grail. Due to practicality, it has often been though as impossible to create a practical on-chip laser using Silicon-compatible group IV semiconductor materials (e.g. germanium) considering their indirect bandgap nature.